PANTOPRAZOLE – DOES IT ENHANCE THE ANTIBACTERIAL EFFICACY OF CALCIUM HYDROXIDE AGAINST ENTEROCOCCUS FAECALIS? - MALATHI SURESH; TEENA ANS ABRAHAM; KESAVARAM PADMAVATHY; KRISHNAN MAHALAKSHMI; ALAGARSAMY VENKATESH; PARAMASIVAM VIVEKANANDHAN; ARUNAJATESAN SUBBIYA; VRIDHACHALAM GANAPATHY SUKUMARAN (International Journal of Pharma and Bio Sciences, 2015)
This study is aimed to evaluate the in vitro efficacy of the association of pantoprazole (proton pump inhibitor) with calcium hydroxide (intracanal medicament) to eliminate the principal endodontic pathogen, Enterococcus faecalis. The antibacterial efficacy of three test solutions, 29% Calcium hydroxide (group I), - 29%Ca(OH)2 with Pantoprazole 2mg/ml (group II) and 29%Ca(OH)2 with Pantoprazole 4mg/ml (group III) was evaluated using the agar diffusion assay. 2%chlorhexidine (group IV) and sterile saline (group V) served as the positive and negative control respectively. The minimum inhibitory concentration (MIC) was determined by Broth microdilution assay. Agar diffusion assay showed zones of inhibition for groups I and IV. Chlorhexidine showed the maximum zone of inhibition compared to the other experimental groups. The MIC values - groups I, II and IV were 0.45 %, 0.45 % + 0.03 mg/ml, ≤ 0.01% respectively. The addition of the proton pump inhibitor- pantoprazole with Ca(OH)2 does not enhance the antimicrobial efficacy of Ca(OH)2.